Lead-barium titanate-based thermal sensitive ceramic powder and preparation method thereof
By adopting a core-shell structure in a lead-barium titanate-based thermosensitive ceramic material, combining the core layer of lead tetroxide and titanium dioxide with the shell layer of modified BaTiO3-based material, the material's voltage resistance under high operating voltage is solved. problem, and achieves low room temperature resistivity, high Curie point and excellent PTC effect.
Patent Information
- Application Number
- CN202411451390.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lead barium titanate-based thermosensitive ceramic materials lack sufficient voltage resistance under high operating voltage environments, and it is difficult to take into account the low room temperature resistivity, high Curie point and excellent positive temperature coefficient (PTC) effects.
The titanium leader-based thermal ceramic powder with a nuclear-shell structure is used in the nuclear layer to use tetraoxide trimer and titanium dioxide, and add 钡, tin, oxide chloride, calcium, mullet, titanium, titanium titanium to the shell layer , Manganese and oxalic acid 素 elements to form a modified BATIO3 base material, which is evenly covered with the surface of the PBTIO3.
The high -resistant voltage characteristics of ceramic materials under high operating voltage are realized, while maintaining low room temperature resistivity, high -ranking library point, and excellent PTC effect.
Smart Images

Figure CN119330709A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material science and technology, and in particular to a lead barium titanate-based thermal-sensitive ceramic powder and a preparation method thereof, in particular to a lead barium titanate-based thermal-sensitive ceramic powder with a core-shell structure and a preparation method thereof. Background Art
[0002] Barium titanate-based positive temperature coefficient (PTC) ceramics are an important electronic ceramic material. Their electrical characteristics are that when the temperature is lower than the Curie temperature, the ceramics maintain a low resistance, and when the temperature is higher than the Curie temperature, the resistance increases by an order of magnitude. PTC ceramics can serve as heating component materials and are widely used in electrical appliances such as electric blankets, electric water heaters, and air conditioners. The working voltage of the above household scenarios is generally 220V. With the rapid development of new energy vehicles in recent years, the operating voltage of PTC heaters is as high as 600V, which requires PTC materials to have sufficient voltage resistance. At the same time, improving the voltage resistance and reducing the size of the heating device is in line with the development trend of device miniaturization. Therefore, the development of high-voltage-resistant PTC materials can effectively promote the development of new energy vehicles and other related fields.
[0003] Pure BaTiO3 ceramics are insulators and have no obvious PTC effect. In order to improve the PTC effect of ceramics, trace donor and acceptor elements are often added to BaTiO3 ceramics to improve the room temperature resistance and lift-to-resistance ratio of ceramics, so as to obtain BaTiO3-based ceramics with good PTC performance. Common donor elements include Y, La, Nd, etc. Luo Chunyuan et al. added Y, La, and Nb elements to pure BaTiO3 respectively, and compared and found that the minimum resistivity was 22.90Ω·cm when Nb was added; common acceptor elements include Mn, Cu, etc. Jin Wei added Cu to BaTiO3 to obtain PTC ceramics with a lift-to-resistance ratio of 5.1×104. Huang Ping et al. added Mn on the basis of Nb addition to prepare barium titanate-based ceramics with a room temperature resistivity of 30.6Ω·cm and a lift-to-resistance ratio of 3.21×106. Mn is better for improving the lift-to-resistance ratio. In addition, the Curie temperature of barium titanate is relatively low, about 120°C. In order to act as a heating device, a Curie point mobile agent needs to be added to increase the Curie temperature. Pb can be dissolved into BaTiO3 to form PbTiO3 (the Curie temperature is about 450°C), thereby increasing the Curie temperature of BaTiO3-based ceramics. At present, the voltage resistance of PTC ceramics has not been mentioned in the research of lead barium titanate-based thermistor ceramics with low room temperature resistivity and high Curie point. Therefore, a lead barium titanate-based thermistor ceramic powder with a core-shell structure and a preparation method thereof are proposed to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a lead barium titanate-based thermistor ceramic powder and a preparation method thereof, so that the sintered ceramic has low room temperature resistivity, high Curie point, excellent PTC effect, and high voltage resistance.
[0005] To achieve the above object, the present invention provides the following technical solution: a lead barium titanate-based thermal-sensitive ceramic powder having a core-shell structure; the raw materials of the core layer are composed of 2 to 7 parts of lead tetroxide and 6 to 21 parts of titanium dioxide in molar proportion; the raw materials of the shell layer are composed of 22 to 42 parts of barium compounds, 1 to 10 parts of tin compounds, 0.5 to 6 parts of zirconium oxychloride, 0.5 to 8 parts of calcium compounds, 0.1 to 4 parts of strontium compounds, 29 to 44 parts of titanium compounds, 0.02 to 0.3 parts of manganese compounds, and 0.1 to 0.5 parts of niobium oxalate;
[0006] As a preferred embodiment, the molar ratio of lead tetroxide to titanium dioxide in the core layer raw material is 1:3.
[0007] Preferably, the barium compound is one or more of barium nitrate, barium chloride, and barium acetate, the tin compound is one or both of tin nitrate and tin tetrachloride, the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate, the strontium compound is one or more of strontium nitrate, strontium chloride, and strontium acetate, the titanium compound is one or both of titanium tetrachloride and tetrabutyl titanate, and the manganese compound is one or more of manganese nitrate, manganese chloride, and manganese acetate.
[0008] A method for preparing lead barium titanate-based thermal sensitive ceramic powder,
[0009] (1) weighing a certain amount of lead tetroxide and titanium dioxide according to the ratio of the core layer raw materials, then placing the lead tetroxide, titanium dioxide and anhydrous ethanol in a ceramic ball mill, adding zirconium oxide grinding balls for ball milling, placing the ball-milled slurry in an oven at 80° C. to dry for 4 to 6 hours, then placing it in an alumina crucible and keeping it at 900 to 1000° C. for 2 to 4 hours, and obtaining PbTiO3 powder after cooling;
[0010] (2) weighing a certain amount of barium compound, tin compound, zirconium oxychloride, calcium compound, strontium compound, titanium compound, manganese compound, and niobium oxalate according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.5-3 mol / L deionized water solution;
[0011] (3) placing the PbTiO3 powder prepared in step (1) and the deionized water solution prepared in step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 950-1050° C. for 2-4 hours;
[0012] (4) The calcined powder is placed in a ball mill, and a 5% by weight aqueous solution of polyvinyl alcohol is added in an amount twice the weight of the powder. After ball milling and mixing, spray granulation is performed to obtain barium lead titanate-based thermistor ceramic powder.
[0013] Beneficial effects of the present invention: The core-shell structure prepared by the present invention with PbTiO3 as the core and the modified BaTiO3 as the shell can make the modified BaTiO3-based material uniformly coated on the surface of PbTiO3, and at the same time, by adding elements such as Sn, Zr, Ca and the like to the BaTiO3 matrix of the shell layer to refine the grains, and adding Mn and Nb elements to improve the PTC effect, so that the powder of the present invention has a high Curie point, excellent PTC effect, and high voltage resistance after sintering into ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a scanning electron microscope image of the lead barium titanate-based thermosensitive ceramic powder prepared by the present invention.
[0015] Figure 2 The figure is an X-ray diffraction diagram of the lead barium titanate-based thermosensitive ceramic powder prepared by the present invention.
[0016] Figure 3 The figure is a resistance-temperature characteristic curve of the lead barium titanate-based thermistor ceramic powder prepared by the present invention after being prepared into ceramics. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Embodiment 1:
[0019] Weigh 4 parts of lead tetroxide and 12 parts of titanium dioxide according to the molar ratio, then place them together with anhydrous ethanol in a ceramic ball mill, and add zirconium oxide grinding balls for ball milling. Place the ball-milled slurry in an oven at 80°C to dry for 4 hours, then place it in an alumina crucible and keep it at 1000°C for 2 hours, and obtain PbTiO3 powder after cooling.
[0020] 33.5 parts of barium nitrate, 1 part of tin nitrate, 6 parts of zirconium oxychloride, 0.5 parts of calcium nitrate, 1 part of strontium nitrate, 41.6 parts of titanium tetrachloride, 0.1 parts of manganese nitrate, and 0.3 parts of niobium oxalate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 2 mol / L deionized aqueous solution.
[0021] The prepared PbTiO3 powder and deionized water solution are placed in a ball mill for ball milling, and then spray dried; the spray dried powder is placed in an alumina crucible and calcined at 1000°C for 3 hours; the calcined powder is placed in a ball mill, and a 5% by weight polyvinyl alcohol aqueous solution is added in a proportion of twice the mass of the powder, and the mixture is ball milled and spray granulated to obtain barium lead titanate-based thermistor ceramic powder.
[0022] The scanning electron microscope image of the lead barium titanate-based thermal sensitive ceramic powder prepared in Example 1 is as follows: Figure 1 Its X-ray diffraction pattern is shown in Figure 2 shown.
[0023] To test the performance of the powder, 2.5 grams of powder was weighed and placed in a mold with a diameter of 18 mm, and then a disc-shaped embryo was made under a pressure of 300 MPa. The embryo was placed in a sintering furnace, and the temperature was increased from room temperature to 450°C at a heating rate of 3°C / min, and kept at 450°C for 120 minutes for debinding, and then the temperature was increased to 1310°C at a heating rate of 5°C / min and kept for 1 hour. After cooling in the furnace, a ceramic sample was obtained. The two sides of the ceramic sample were polished and coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation. The ceramic sample was then subjected to resistance-temperature test and voltage withstand test, and its performance parameters are as follows Figure 3 As shown in Table 1.
[0024] Embodiment 2:
[0025] 7 parts of lead tetroxide and 21 parts of titanium dioxide were weighed according to the molar ratio, and then placed in a ceramic ball mill together with anhydrous ethanol. Zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C and dried for 5 hours. It was then placed in an alumina crucible and kept at 900°C for 4 hours. PbTiO3 powder was obtained after cooling.
[0026] 26.4 parts of barium nitrate, 5 parts of tin nitrate, 0.5 parts of zirconium oxychloride, 4 parts of calcium nitrate, 0.1 parts of strontium nitrate, 35.2 parts of titanium tetrachloride, 0.3 parts of manganese nitrate, and 0.5 parts of niobium oxalate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 3 mol / L deionized aqueous solution.
[0027] The prepared PbTiO3 powder and deionized water solution are placed in a ball mill for ball milling, and then spray dried; the spray dried powder is placed in an alumina crucible and calcined at 950°C for 4 hours; the calcined powder is placed in a ball mill, and a 5% by weight polyvinyl alcohol aqueous solution is added in a proportion of twice the mass of the powder, and the mixture is ball milled and spray granulated to obtain barium lead titanate-based thermistor ceramic powder.
[0028] To test the performance of the powder, 2.5 grams of powder was weighed and placed in a mold with a diameter of 18 mm, and then a disc-shaped embryo was made under a pressure of 300 MPa. The embryo was placed in a sintering furnace, heated from room temperature to 450°C at a heating rate of 3°C / min, kept at 450°C for 120 minutes for debinding, and then heated to 1310°C at a heating rate of 5°C / min and kept for 1 hour. After cooling with the furnace, a ceramic sample was obtained. The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation. The ceramic sample was then subjected to resistance-temperature test and withstand voltage test, and its performance parameters are shown in Table 1.
[0029] Embodiment 3:
[0030] 2 parts of lead tetroxide and 6 parts of titanium dioxide were weighed according to the molar ratio, and then placed in a ceramic ball mill together with anhydrous ethanol. Zirconium oxide grinding balls were added for ball milling. The ball-milled slurry was placed in an oven at 80°C for 6 hours and then placed in an alumina crucible for 3 hours at 950°C. PbTiO3 powder was obtained after cooling.
[0031] 38 parts of barium nitrate, 2 parts of tin nitrate, 1 part of zirconium oxychloride, 1 part of calcium nitrate, 4 parts of strontium nitrate, 45.6 parts of titanium tetrachloride, 0.2 parts of manganese nitrate, and 0.2 parts of niobium oxalate were weighed according to the molar ratio, and then dissolved in deionized water to obtain a 0.5 mol / L deionized water solution.
[0032] The prepared PbTiO3 powder and deionized water solution are placed in a ball mill for ball milling, and then spray dried; the spray dried powder is placed in an alumina crucible and calcined at 1050°C for 2 hours; the calcined powder is placed in a ball mill, and a 5% polyvinyl alcohol aqueous solution is added in a proportion of twice the mass of the powder. After ball milling, the mixture is spray granulated to obtain barium lead titanate-based thermistor ceramic powder.
[0033] To test the performance of the powder, 2.5 grams of powder was weighed and placed in a mold with a diameter of 18 mm, and then a disc-shaped embryo was made under a pressure of 300 MPa. The embryo was placed in a sintering furnace, heated from room temperature to 450°C at a heating rate of 3°C / min, kept at 450°C for 120 minutes for debinding, and then heated to 1310°C at a heating rate of 5°C / min and kept for 1 hour. After cooling with the furnace, a ceramic sample was obtained. The two sides of the ceramic sample were polished, coated with ohmic silver paste and kept at 550°C for 30 minutes to complete the electrode preparation. The ceramic sample was then subjected to resistance-temperature test and withstand voltage test, and its performance parameters are shown in Table 1.
[0034] Table 1 Electrical properties of the lead barium titanate-based thermistor ceramic powder prepared by the present invention after being prepared into ceramics
[0035]
Claims
1. A lead barium titanate-based thermal-sensitive ceramic powder, characterized in that: It has a core-shell structure; the raw materials of the core layer are composed of 2 to 7 parts by mole ratio of lead tetroxide and 6 to 21 parts by mole ratio of titanium dioxide; The molar proportions of the raw materials of its shell are as follows: 22 to 42 parts of barium compounds, 1 to 10 parts of tin compounds, 0.5 to 6 parts of zirconium oxychloride, 0.5 to 8 parts of calcium compounds, 0.1 to 4 parts of strontium compounds, 29 to 44 parts of titanium compounds, 0.02 to 0.3 parts of manganese compounds, and 0.1 to 0.5 parts of niobium oxalate.
2. The lead barium titanate-based thermal-sensitive ceramic powder according to claim 1, characterized in that: The molar ratio of lead tetroxide to titanium dioxide in the core layer raw materials is 1:
3.
3. The lead barium titanate-based thermal-sensitive ceramic powder according to claim 1, characterized in that: The barium compound is one or more of barium nitrate, barium chloride, and barium acetate, the tin compound is one or both of tin nitrate and tin tetrachloride, the calcium compound is one or more of calcium nitrate, calcium chloride, and calcium acetate, the strontium compound is one or more of strontium nitrate, strontium chloride, and strontium acetate, the titanium compound is one or both of titanium tetrachloride and tetrabutyl titanate, and the manganese compound is one or more of manganese nitrate, manganese chloride, and manganese acetate.
4. A method for preparing lead barium titanate-based thermal-sensitive ceramic powder, characterized in that: (1) weighing a certain amount of lead tetroxide and titanium dioxide according to the ratio of the core layer raw materials, then placing the lead tetroxide, titanium dioxide and anhydrous ethanol in a ceramic ball mill, adding zirconium oxide grinding balls for ball milling, placing the ball-milled slurry in an oven at 80° C. to dry for 4 to 6 hours, then placing it in an alumina crucible and keeping it at 900 to 1000° C. for 2 to 4 hours, and obtaining PbTiO3 powder after cooling; (2) weighing a certain amount of barium compound, tin compound, zirconium oxychloride, calcium compound, strontium compound, titanium compound, manganese compound, and niobium oxalate according to the ratio of the shell raw materials, and then dissolving the above compounds in deionized water to obtain a 0.5-3 mol / L deionized water solution; (3) placing the PbTiO3 powder prepared in step (1) and the deionized water solution prepared in step (2) in a ball mill for ball milling, and then spray drying; placing the spray-dried powder in an alumina crucible, and calcining it at 950-1050° C. for 2-4 hours; (4) The calcined powder is placed in a ball mill, and a 5% by weight aqueous solution of polyvinyl alcohol is added in an amount twice the weight of the powder. After ball milling and mixing, spray granulation is performed to obtain barium lead titanate-based thermistor ceramic powder.
Citation Information
Patent Citations
Ceramic dielectric material of barium titanate core-strontium / zirconium / calcium shell structure and preparation method thereof
CN107739205A
PTC thermistor
CN108766692A
Method for improving reduction resistance of PTC (Positive Temperature Coefficient) thermosensitive element
CN114496432A
Composite material and ceramic for PTC thermistor and manufacture thereof
CN1247842A
Cold conductor material used for electronic switches consists of a finely dispersed titanate powder and a structure made up of a core of lead titanate and a shell of barium titanate, calcium titanate or strontium titanate
DE10045394A1